Ultrasonography of Optic Nerve Sheath Diameter in Healthy Volunteers - Ariel Sosa Remón; Wilfredo Boch Rodríguez; Dasha María García Arias; Carmen Esther Remón Chávez; Ana Esperanza Jerez Álvarez; Arian Jesús Cuba Naranjo (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: ultrasonography of the diameter of the optic nerve sheath has been used as a non-invasive measure of intracranial pressure. One of the deficiencies stated is the non-existence of a standard value that suggests the limit between normality and intracranial hypertension. Objective: determine the diameter of the optic nerve sheath using ultrasound in healthy volunteers. Methods: a multi-population ecological study was conducted on 160 healthy volunteers who met the inclusion criteria. Three ultrasonographic measurements were performed in B mode in each eye, the average was taken as the final value. The variables studied were: age, sex, skin color and diameter of the optic nerve sheath. The percentage, mean, median, limit and standard were calculated. With a reference value at the 95 % confidence interval. The relationship between the variables was determined by simple logistic regression analysis with the SPSS 22.0 statistical package. Results: that diameter of the optic nerve sheath, in the subjects, was quantified between 4.62-4.80 mm and 4.66-4.83 mm for the right and left eyes respectively. In the simple linear regression analysis, only sex was associated with the value of the diameter of the optic nerve sheath (p= 0.000). Conclusions: in a population of healthy volunteers, the value of the diameter of the optic nerve sheath was similar to other descriptions, with differences between sex, which suggests taking this variable into consideration when making the measurement.